Excellence and leadership with Vision, Inspiration and Integrity (Journal of Universal Excellence, 2026)
Research Question (RQ): How the way of leadership with Vision, Inspiration and Integrity affects the organizations and its employees.Purpose: To explore the relationships between all three factors of the EFQM Excellence Model, Leadership with Vision, Inspiration, and Integrity, to identify whether one of the three factors is more crucial than the other two.Method: We used a descriptive method where we collected literature and information, reviewed and analyzed it.Results: The research found that all three segments are important for the Leadership with Vision, Inspiration and Integrity building block, as such a way of holistic leadership is key to the success of the organizations and employees satisfaction.Organization: The research provided the organizations with a clear guidelines and an overview of the most appropriate management methods, which are key to the organizations excellence and employees satisfaction. At the same time, we also confirmed good examples of practice that are already well established in the organizations.Society: The social responsibility of an organization, where the way of leadership is as defined by the EFQM model, is great and is also reflected in society itself.Originality: The research is of great importance for the organizations in which we conducted a self-assessment according to the FOŠmeter of business excellence and consequently made proposals for improving the mentioned Model.Limitations/Future Research: The limitations of the research are mainly in terms of addressing only one of the eight building blocks of the EFQM excellence model and analysis of self-assessment results for a period of only one year, so it would make sense to extend the analysis.
Keywords: organization; leadership; EFQM; vision; integrity; inspiration; FOŠmeter; excellence